AN ANALYSIS OF NOUN PHRASE USAGE IN THE KOMPAS.ID SHORT STORY SECTION (JANUARY–MARCH 2024) AND ITS PEDAGOGICAL IMPLICATIONS IN SHORT STORY TEXT LEARNING - Shintia Putri Melati; Siti Ainim Liusti, Siti (Universitas Muhammadiyah Makassar, 2025)
This study examines the use of noun phrases in the Kompas.id short story section published between January and March 2024 and explores its implications for teaching short story texts in schools. The study is motivated by the importance of linguistic analysis in understanding syntactic structures within modern literary works, particularly the role of noun phrases as key elements in shaping narrative meaning. The research aims to describe the syntactic functions of noun phrases, analyze the semantic relationships among their components, and identify the structural patterns used in the texts. A qualitative descriptive approach was employed, with data collected through close reading and note-taking techniques applied to twenty short stories published during the research period. The data were analyzed through the stages of reduction, classification, and interpretation using syntactic theories proposed by Ramlan (2005), Alwi et al. (2014), and Kridalaksana (2011). The results indicate that noun phrases in Kompas.id short stories exhibit a range of syntactic functions, with the subject and adverbial functions being most dominant, while the complement function occurred least frequently. The most common semantic relationships identified were quantitative and additive, whereas the prevailing structural pattern was FN/N + N/FN. These findings confirm that noun phrases not only serve grammatical purposes but also carry stylistic and semantic significance in enhancing description and narrative imagery. Pedagogically, the results suggest that noun phrase analysis can be integrated into short story instruction to strengthen students’ linguistic awareness and narrative writing skills.